Analisis Pengaruh Kelengkapan Produk dan Visual Merchandising terhadap Keputusan Pembelian Konsumen - Mitha Tri Mutiar; Acep Samsudin; Dicky Jhoansyah (Journal of Management and Bussines (JOMB), 2022)
The purpose of this study was to measure the effect of product completeness and visual merchandising on consumer purchasing decisions at PO Restu Mekar, Sukabumi Regency. This research method is descriptive quantitative. This type of sampling is included in the random sampling sample by distributing questionnaires to 90 consumers. The analysis technique used is multiple linear regression analysis, including the coefficient of determination test, multiple correlation coefficient and simultaneous test (F test). The results showed that the coefficient of determination test seen from the value (Adjusted R2) of 0.940 means that the effect of product completeness and visual merchandising on purchasing decisions is 88% and 12% is influenced by other factors not explained in the study. Based on the F test the probability value of sig 0.00 < 0.01. In conclusion, together the value of product completeness and Visual merchandising have a significant effect on consumer purchasing decisions. Keywords: Product Completeness, Consumer Purchase Decision, Visual Merchadising